2018
DOI: 10.1123/ijsnem.2017-0272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 4-Week Ingestion of Tomato-Based Carotenoids on Exercise-Induced Inflammation, Muscle Damage, and Oxidative Stress in Endurance Runners

Abstract: This double-blind, randomized, placebo-controlled crossover trial determined if ingestion of a supplement containing a tomato complex with lycopene, phytoene, and phytofluene (T-LPP) and other compounds for 4 weeks would attenuate inflammation, muscle damage, and oxidative stress postexercise and during recovery from a 2-hr running bout that included 30 min of -10% downhill running. Study participants ingested the T-LPP supplement or placebo with the evening meal for 4 weeks prior to running 2 hr at high inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…In contrast, the present study did not reveal a significant difference in exercise-induced Mb elevation between trials, suggesting that repeated-cycling exercise (short duration of exercise) in moderate hypoxia did not trigger a further increase in muscle damage markers compared with the same exercise in normoxia. However, because exercise using a cycle ergometer mainly consisting of concentric muscle contraction, exercise-induced Mb elevation was relatively lower than that reported in previous studies using running exercise, which involves eccentric muscle contraction (Nieman et al, 2018; Sumi et al, 2018). Moreover, exercise mode (running or cycling) might be one of the factors supporting elevation for shear stress.…”
Section: Discussionmentioning
confidence: 57%
“…In contrast, the present study did not reveal a significant difference in exercise-induced Mb elevation between trials, suggesting that repeated-cycling exercise (short duration of exercise) in moderate hypoxia did not trigger a further increase in muscle damage markers compared with the same exercise in normoxia. However, because exercise using a cycle ergometer mainly consisting of concentric muscle contraction, exercise-induced Mb elevation was relatively lower than that reported in previous studies using running exercise, which involves eccentric muscle contraction (Nieman et al, 2018; Sumi et al, 2018). Moreover, exercise mode (running or cycling) might be one of the factors supporting elevation for shear stress.…”
Section: Discussionmentioning
confidence: 57%
“…In ten intervention studies, biomarkers of inflammation were not reported to change after tomato/lycopene supplementation [ 59 , 62 , 64 , 66 , 67 , 68 , 70 , 73 , 74 , 75 ]. On the contrary, in a study by Li et al [ 60 ], tomato juice supplementation led to a decrease of inflammatory adipokine MCP-1, and an increase in anti-inflammatory adiponectin levels in healthy Taiwanese females (20–30 years).…”
Section: Resultsmentioning
confidence: 99%
“…Six included intervention studies evaluated possible associations between lycopene/tomato supplementation and inflammation in healthy participants. In three of these studies, markers of inflammation did not change after supplementation, although circulating lycopene had increased by about 50 percent [ 59 , 64 , 69 ]. However, in another study the lycopene concentration also increased 1.5 times, and a significant decrease in hs-CRP was observed [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Carotenoids act as antioxidants in the human body, helping to maintain an antioxidant–ROS balance which can help improve physical performance. Nieman et al [ 28 ] reported that increased levels of carotenoids in the blood reduces muscle damage. In a study of Spanish adolescents, higher concentrations of vitamin C in male adolescents and β-carotene in female adolescents were positively associated with maximal oxygen consumption, and higher concentrations of β-carotene and α-tocopherol in male adolescents and β-carotene in female adolescents were associated with better performance in the standing long jump test [ 12 ].…”
Section: Discussionmentioning
confidence: 99%